Meniscus Matrix Remodeling in Response to Compressive Forces in Dogs - Umberto Polito; Giuseppe M. Peretti; Mauro Di Giancamillo; Federica Boschetti; Liliana Carnevale; Maria C. Veronesi; Luca M. Sconfienza; Marco Agnoletto; Laura Mangiavini; Silvia C. Modina; Alessia Di Giancamillo (Cells, 2020)
Joint motion and postnatal stress of weight bearing are the principal factors that determine the phenotypical and architectural changes that characterize the maturation process of the meniscus. In this study, the effect of compressive forces on the meniscus will be evaluated in a litter of 12 Dobermann Pinschers, of approximately 2 months of age, euthanized as affected by the quadriceps contracture muscle syndrome of a single limb focusing on extracellular matrix remodeling and cell−extracellular matrix interaction (i.e., meniscal cells maturation, collagen fibers typology and arrangement). The affected limbs were considered as models of continuous compression while the physiologic loaded limbs were considered as controls. The results of this study suggest that a compressive continuous force, applied to the native meniscal cells, triggers an early maturation of the cellular phenotype, at the expense of the proper organization of collagen fibers. Nevertheless, an application of a compressive force could be useful in the engineering process of meniscal tissue in order to induce a faster achievement of the mature cellular phenotype and, consequently, the earlier production of the fundamental extracellular matrix (ECM), in order to improve cellular viability and adhesion of the cells within a hypothetical synthetic scaffold.